Pengaruh Dwelling Time pada Penerimaan Pajak Impor di Indonesia - Hilal, Adam Syaiful; Lisna, Vera (UI Scholars Hub, 2019)
High dwelling time in Indonesia has been in the spotlight of President since his visit to the Port of Tanjung Priok in 2014. This could bring impact on international trade, one of which is indicated by import tax revenue. The value of import in Indonesia which continues to fall has brought impact to lower country revenue from import tax. The objective of this study is to analyze the effect of dwelling time on import tax revenue in Indonesia. The results from recursive equation system of Error Correction Model (ECM) by using data during January 2014 to November 2016 show that lower dwelling time will increase import tax revenue in Indonesia.